Effect of Heat Treatment and Tempering Process on the Hardness of S55c Steel as A Cutting Blade Material for Plastic Shredding Machines - Yudo, Eko; Ariyanto, Ariyanto; Erwansyah, Erwansyah; Suzen, Zaldy Sirwansyah; Sugiyarto, Sugiyarto; Dharta, Yuli; Zulfitriyanto, Zulfitriyanto (Integrated Science Education Journal, 2026)
Purpose of the study: This study aims to optimize the heat treatment process of S55C medium-carbon steel by examining the combined effects of austenitizing temperature, quenching media, and tempering temperature on impact toughness. Methodology: An experimental approach was employed using quenching and tempering treatments. Quenching was performed at three austenitizing temperatures (950°C, 1000°C, and 1050°C) with three different cooling media—salt water, oil, and seawater—followed by tempering at 100°C, 200°C, 300°C, and 400°C. All heating processes were conducted in an electric furnace. Parameter optimization was carried out using the Taguchi method with an L9 orthogonal array. Mechanical performance was evaluated through Charpy impact testing, and confirmation experiments were conducted to validate the optimal parameter combination. Main Findings: The Taguchi analysis identified the optimal quenching condition at an austenitizing temperature of 1050°C with salt water as the cooling medium, yielding the highest impact toughness. Confirmation tests supported the reliability of this result. Additionally, the tempering process showed that increasing the tempering temperature decreased hardness while significantly improving toughness, indicating effective stress relief and improved ductility in the steel microstructure. Novelty/Originality of this study: The novelty of this study lies in the integrated optimization of quenching temperature and diverse cooling media, including seawater, using the Taguchi method, with a specific focus on toughness rather than hardness alone. This research provides new insights into tailoring heat treatment parameters for S55C steel to achieve superior impact resistance, offering practical guidance for more efficient and application-oriented heat treatment strategies in manufacturing industries.